Evolution and Spatial-temporal Shift Characteristics of Soil Erosion in Yan'An City During 1990—2020 - Xie Mingyang; Jiao Chunmeng; Han Xiaoyu; Jiao Feng (Shuitu baochi tongbao)
[Objective] The temporal and spatial changes in soil erosion intensity when farmland is returned to forest or grassland in Yan'an City Shaanxi Province were analyzed in order to provide a reference for researches on the planning and evaluation of soil and water conservation, land resource management, and ecological restoration. [Methods] Based on the interpretation results of remote sensing images of Yan'an City from 1990 to 2020 and standards for classification and gradation of soil erosion set by the Ministry of Water Resources, PRC (SL190-2007), soil erosion in Yan'an City was analyzed using the shift-share model. [Results] ① The graded change of soil erosion in Yan'an City as a whole was severe in the north and mild in the south, and the year 2000 was the inflection point where the situation changed from aggravated erosion to gradual recovery. The average soil erosion modulus in Yan'an City decreased from a maximum value of 4 071.38 t/(km2·yr) to 2 366.19 t/(km2·yr). ② The overall change of soil erosion was mainly affected by three erosion levels (slight erosion, moderate erosion, and severe erosion). ③ The shift-share model might be useful in exploring the offset effects of the grain for green project on soil erosion in the districts and counties of Yan'an City. Nevertheless, its application needs to be further investigated and improved due to issues such as accuracy and precision, as well as its ecological significance. [Conclusion] The forest land in the north and central part of Yan'an City increased rapidly, while the grassland in the south increased rapidly. The proportional changes among forest land, cultivated land, and grassland with different coverages were the main reason for the periodic changes in soil erosion.